Discrepant prevalence and incidence of Leishmania infection between two neighboring villages in Central Mali based on Leishmanin skin test surveys. - Fabiano Oliveira; Seydou Doumbia; Jennifer M Anderson; Ousmane Faye; Souleymane S Diarra; Pierre Traoré; Moumine Cisse; Guimba Camara; Koureissi Tall; Cheick A Coulibaly; Sibiry Samake; Ibrahim Sissoko; et al. (Public Library of Science (PLoS), 2009)
Apart from a single report, the last publication of cutaneous leishmaniasis (CL) in Mali dates back more than 20 years. The absence of information on the current status of CL in Mali led us to conduct a cohort study in Kemena and Sougoula, two villages in Central Mali from which cases of CL have been recently diagnosed by Mali's reference dermatology center in Bamako. In May 2006, we determined the baseline prevalence of Leishmania infection in the two villages using the leishmanin skin test (LST). LST-negative individuals were then re-tested over two consecutive years to estimate the annual incidence of Leishmania infection. The prevalence of Leishmania infection was significantly higher in Kemena than in Sougoula (45.4% vs. 19.9%; OR: 3.36, CI: 2.66-4.18). The annual incidence of Leishmania infection was also significantly higher in Kemena (18.5% and 17% for 2007 and 2008, respectively) than in Sougoula (5.7% for both years). These data demonstrate that the risk of Leishmania infection was stable in both villages and confirm the initial observation of a significantly higher risk of infection in Kemena (OR: 3.78; CI: 2.45-6.18 in 2007; and OR: 3.36; CI: 1.95-5.8 in 2008; P<0.005). The absence of spatial clustering of LST-positive individuals in both villages indicated that transmission may be occurring anywhere within the villages. Although Kemena and Sougoula are only 5 km apart and share epidemiologic characteristics such as stable transmission and random distribution of LST-positive individuals, they differ markedly in the prevalence and annual incidence of Leishmania infection. Here we establish ongoing transmission of Leishmania in Kemena and Sougoula, Central Mali, and are currently investigating the underlying factors that may be responsible for the discrepant infection rates we observed between them.ClinicalTrials.gov NCT00344084.